Willa Cather and modern cultures - Homestead, Melissa J., 1963-; Reynolds, Guy (Cather studies, 2011)
Linking Willa Cather to "the modern" or "modernism" still seems an eccentric proposition to some people. Born in 1873, Cather felt tied to the past when she witnessed the emergence of twentieth-century modern culture, and the clean, classical sentences in her fiction contrast starkly with the radically experimental prose of prominent modernists. Nevertheless, her representations of place in the modern world reveal Cather as a writer able to imagine a startling range of different cultures. Divided into two sections, the essays in Cather Studies, Volume 9 examine Willa Cather as an author with an innovative receptivity to modern cultures and a powerful affinity with the visual and musical arts. From the interplay between modern and antimodern in her representations of native culture to the music and visual arts that animated her imagination, the essays are unified by an understanding of Cather as a writer of transition whose fiction meditates on the cultural movement from Victorianism into the twentieth century